2004
DOI: 10.1677/erc.0.0110315
|View full text |Cite
|
Sign up to set email alerts
|

FSH and LH serum/tumor fluid ratios and malignant tumors of the ovary.

Abstract: The aim of this work was to compare mean concentrations of gonadotropins in serum and fluid from malignant and benign ovarian tumors. We enrolled 126 patients diagnosed with malignant epithelial tumors (n=40), borderline epithelial tumors (n ¼ 14), benign cystadenomas (n ¼ 28) and simple cysts (n ¼ 44) of the ovary. Premenopausal and postmenopausal subgroups were formed in each group. The concentration of FSH and LH was measured in serum and tumor fluid and the serum/tumor fluid ratio was calculated. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
4
16
1
1
Order By: Relevance
“…To investigate the correlation between FSH, survivin, and HIF-1α, we stimulated SKOV-3 cells with 40 mIU/mL FSH for 0, 8,16,24,48, or 72 h. Western blot analysis showed that the survivin and HIF-1α expression levels increased gradually over time in SKOV-3 cells, peaked at 24 h, and then declined slightly, indicating a time-dependent correlation (Figure 2A and 2B).…”
Section: Fsh Stimulation Of Survivin and Hif-1α Expression In Skov-3 mentioning
confidence: 94%
“…To investigate the correlation between FSH, survivin, and HIF-1α, we stimulated SKOV-3 cells with 40 mIU/mL FSH for 0, 8,16,24,48, or 72 h. Western blot analysis showed that the survivin and HIF-1α expression levels increased gradually over time in SKOV-3 cells, peaked at 24 h, and then declined slightly, indicating a time-dependent correlation (Figure 2A and 2B).…”
Section: Fsh Stimulation Of Survivin and Hif-1α Expression In Skov-3 mentioning
confidence: 94%
“…Additionally, there is a pronounced decrease in the risk of developing epithelial ovarian cancer (EOC) in women using oral contraceptives for more than 10 years, having multiple pregnancies, or having prolonged lactation, all conditions associated with suppressed gonadotropins in the circulation (Gnagy et al 2000, Modugno et al 2004. Of significance, recent studies of ovarian cyst fluid from malignant and benign ovarian tumours have shown higher levels of FSH and LH in fluid from malignant versus benign tumours (Rzepka-Gorska et al 2004, Thomas et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The receptors for follicle-stimulating hormone (FSH) and luteinizing hormone (LH) have been shown in normal and neoplastic ovarian surface epithelium (OSE) cells (13,14). Moreover, levels of ovarian and peritoneal gonadotropins seem to be elevated in ovarian cancer patients (15,16). Together, these observations suggest a possible role of gonadotropins in the development and progression of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%